Sonographischer Vergleich der Halsstreckmuskeldicke von Patienten mit ankylosierender Spondylitis und nicht-röntgenologischer axialer Spondyloarthritis mit gesunden Probanden - Karabaş, Çağlar; Aras, Berke; Erol, Kemal; Kuzu, Ömer (Aktuelle Rheumatologie, 2022)
Introduction This study examines the neck extensor muscle thickness of patients with ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA) by comparing them with healthy volunteers. It also aims to evaluate the relationship between muscle thickness and disease activity, functional parameters, neck disability and quality of life in patients with AxSpA.Method In this cross-sectional study, 30 patients with AS and 30 patients with nr-AxSpA who were admitted to a Physical Medicine and Rehabilitation outpatient clinic were included consecutively. Thirty healthy participants were included as a control group. The thickness of muscles was measured bilaterally by ultrasound and the muscle thickness average was recorded. All patients with axSpA were asked to complete the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), the Bath Ankylosing Spondylitis Metrology Index (BASMI), the Ankylosing spondylitis Quality of Life (AsQoL) scale and the Neck Disability Index (NDI).Results Mean patient age was 42.36±10.0 in the AS group, 38.13±7.94 in the nr-axSpA group and 39.06±8.25 in the healthy group. A statistically significant decrease was found in multifidus, semispinalis capitis, semispinalis cervicis and splenius capitis muscle thickness in AS patients compared with the healthy group, and in semispinalis cervicis muscle thickness in nr-axSpA patients compared with the healthy group. However, when trapezius muscle thickness was compared between the groups, no statistical difference was found. There was a significant negative correlation between neck extensor muscle thickness and age, BASDAI, NDI and AsQoL in patients with axSpA.Conclusion The thickness of the neck extensor muscles is decreased in patients with AxSpA compared with healthy individuals, and this situation can be reliably detected by ultrasound.
Keywords: ankylosing spondylitis; non-radiographic axial spondyloarthritis; neck muscle; ultrasound; axial spondyloarthritis